Inisiasi Menyusu Dini dan Pencapaian Involusi Uterus pada Ibu Postpartum - Riska Hediya Putri; Surmiasih Surmiasih; Feri Kameliawati; Hanna Afifah (Universitas Faletehan, 2020)
Postpartum hemorrhage gets the highest rank in the maternal mortality rate. One of the causes is uterine atony. Early initiation of breastfeeding can induce posterior lobe of pituitary gland to secret oxytocin. Oxytocin accelerates the involution process and minimizes blood loss. The research aims to identify the effects of early initiation of breastfeeding on uterine involution process in post-partum mothers. It is a quantitative research with quasi-experimental research design. The samples are postpartum mothers, 16 cases and 16 controls. The sampling technique used consecutive sampling. The data analysis used independent t-test. The results of the research found that the post-partum mothers who did early initiation of breastfeeding after two hours had the average of fundal height 3.13 cm below bellybutton and after twelve hours had the average of 2.13 cm below bellybutton. The group that did not do early initiation of breastfeeding after two hours and twelve hours got the same result of average 1.63 cm below bellybutton. The results of the bivariate analysis in both groups after two hours got p-value 0.000 and after twelve hours obtained p-value 0.030. It can be concluded that there is an effect of early initiation of breastfeeding on uterine involution process in post-partum mothers. Thus, the researchers suggested to make early initiation of breastfeeding as a standard operational procedure in childbirth service.